Ravinas: processo de formação e desenvolvimento - Guerra, Antonio José Teixeira (Anuário do Instituto de Geociências, 1997)
The present paper concerns rill initiation and evolution, taking into account its role on the erosion process. Therefore, several aspects of the process are developed, such as: the process itself, evidences of the process, through field and laboratory experiments, the importance of the models, the consequences to agricultural soils and the conectivity with other soil erosion processes.